Stakeholders’ perceptions, acceptability, and sustainability of a larviciding intervention in Tanga Region, Tanzania - Kihwele, Fadhila; Gavana, Tegemeo; Kailembo, Denis; Kasagama, Elizabeth; Mwalimu, Charles Dismas; Bernard, Jubilate; Yoram, Best; Ndekuka, Leah; Kajange, Stella; Lazaro, Samwel; Kisoka, Noela; Chaki, Prosper; et al. (Frontiers in Malaria, 2025)
BackgroundIn 2019, the Government of Tanzania endorsed the countrywide implementation of mosquito larviciding to complement insecticide-treated nets (ITNs) and indoor residual spraying (IRS) as vector control interventions. Between 2022 and 2024, a large-scale pilot project covering a population of over 1 million individuals was implemented in the Tanga Region, in the northeast of the country. The program was implemented entirely by the government system and made use of community-owned resource persons (CORPs). This manuscript presents the key results of a qualitative study assessing the perceptions and awareness of the stakeholders and the acceptability, facilitating factors, barriers, and sustainability of the intervention. Companion publications report on the operations, entomological and epidemiological impacts, and costs of the program.MethodologyThis cross-sectional qualitative study used in-depth interviews (IDIs) and focus group discussions (FGDs) to assess perceptions, acceptability, and sustainability regarding larviciding. A total of 44 IDIs were conducted with government officials who oversaw project implementation. In addition, 13 FGDs were held with 156 community participants(72 CORPs involved in larviciding activities and 84 other community members). Data were analyzed using framework analysis.ResultsThe study findings showed that community-based larviciding was perceived as safe, acceptable, effective, feasible, and sustainable. However, several key challenges were identified, including the unpleasant smell of the larvicide, the CORP turnover, logistic problems, and discontinuous implementation.ConclusionThe pilot larviciding intervention implemented in the Tanga Region was perceived as safe, effective, feasible, and sustainable, and was widely accepted by the community. However, addressing key operational challenges such as the unpleasant odor of the larvicide, high CORP turnover, logistical constraints, and discontinuous implementation will be essential to ensuring the effectiveness and sustainability of future large-scale rollouts.